A Cascading Evaluation of Digital Population Identity in Palembang: Insights from ILPE and IPA - Fadly, Farid; Kholik, Abdul; Alie, Muhammad F.; Heryati, Agustina; Terttiaavini, Terttiaavini; Antoni, Darius (Intelligent System and Computation, 2024)
Since 2022, the Indonesian government has implemented the Digital Population Identity (IKD) application, introduced by the Palembang City Population and Civil Registration Office (Disdukcapil). However, user satisfaction with IKD remains low. This study evaluates IKD user satisfaction using a cascading method combining the Electronic Public Service Index (ILPE) and Importance Performance Analysis (IPA). The ILPE calculation yields a total score of 2.682. The Information Availability (I) dimension scores highest at 0.570, reflecting strong user satisfaction with data accuracy and relevance. In contrast, the Interaction (SI) dimension scores the lowest at 0.325, highlighting the need for better communication and interaction. The IPA analysis categorizes dimensions into quadrants: Quadrant 1 (Keep Up the Good Work) includes T1 (Password Security), T4 (Reputation Recognition), T5 (Clarity of Authentication Criteria), I1 (Data Accuracy), I2 (Timely Updates), R2 (Access Availability), and R3 (Response Speed), showing excellent performance. Quadrant 2 (Concentrate Here) includes E4 (Accuracy of Data Entry Instructions) and U3 (Intuitive Navigation), requiring significant improvement. Quadrant 3 (Low Priority) includes E1 (Intuitive Navigation), E3 (Personalized Experience), T2 (Authentication Clarity), U1 (Intuitive Interface), U2 (Instruction Clarity), SI1 (Social Interaction), and SI2 (Communication Ease), with lower improvement priorities. Quadrant 4 (Possibly Overrated) contains R1 (Form Download Speed), which may be overemphasized. These findings aim to guide policy refinement, enhance public service efficiency, and improve user satisfaction.